PENGARUH BRAND EQUITY, PERSEPSI HARGA DAN DISTRIBUSI TERHADAP KEPUASAN PELANGGAN PRODUK PAKAIAN MEREK OLD BLUE COMPANY - Ludfi Mariadi; Havidz Aima (Universitas Mercu Buana, 2014)
Abstract: This thesis aims is to know effect of brand equity, perceived price, and distribution to customer satisfaction on apparel brand Oldblue Company. The method that used is an explanatory analysis by data collection through literature review, observation, and interviews. This observation found that perceived price variables has no significant effect on customer satisfaction, while other variables, brand equity anddistribution in individually and simultaneously have significant effect on customer satisfaction. Brand feelings or self-confidence that is felt by customers when wearing Oldblue products make customers feel satisfied and make Oldblue as preferred customer favorite products. The availability of the product in Oldblue retailers make customers feel satisfied and created customers’ loyalty, so that customers do not needto switch to another brand to get the product that suits with them because retailers of Oldblue always provide it. Brand equity and distribution affected customer satisfaction at 56.3%, so the remaining 43.7% is influenced by other variables not that not observed.Keywords: Brand Equity, Perceived Price, Distribution, Customer Satisfaction